Chiral quantum supercrystals with total dissymmetry of optical response - GOUNKO, IOURI (My University, 2016)
Since chiral nanoparticles are much smaller than the optical wavelength, their enantiomers show little difference in the interaction with circularly polarized light. This scale mismatch makes the enhancement of enantioselectivity in optical excitation of nanoobjects a fundamental challenge in modern nanophotonics. Here we demonstrate that a strong dissymmetry of optical response from achiral nanoobjects can be achieved through their arrangement into chiral superstructures with the length scale comparable to the optical wavelength. This concept is illustrated by the example of the simple helix supercrystal made of semiconductor quantum dots. We show that this supercrystal almost fully absorbs light with one circular polarization and does not absorb the other. The giant circular dichroism of the supercrystal comes from the formation of chiral bright excitons, which are the optically active collective excitations of the entire supercrystal. Owing to the recent advances in assembly and self-organization of nanocrystals in large superparticle structures, the proposed principle of enantioselectivity enhancement has great potential of benefiting various chiral and analytical methods, which are used in biophysics, chemistry, and pharmaceutical science.
PUBLISHED
Cited By :3 Export Date: 28 February 2017
Keywords: chiral nanoparticles; chiral nanoparticles